UPAYA GURU DALAM MENANGANI PERILAKU KENAKALAN SISWA SD - Sumani, Sumani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to describe (1) Forms of delinquency behavior of students in elementary school (2) Factors causing delinquency of students in elementary school (3) Efforts of teachers to deal with delinquent behavior in elementary school students (4) Teacher barriers in dealing with student misbehavior at elementary school. This type of research is qualitative research. Data collection techniques used by researchers are observation, interviews and documentation. The results of this study indicate (1) forms of student delinquency such as; hiding friends' belongings, fighting, crowded, skipping or not going to school without nosy information, calling his friend's name as the name of his parents, and uploading pictures that were not good on Facebook. (2) causative factors, namely from endogenous factors and exogenous factors (3) The teacher's efforts in dealing with student misbehavior, namely giving advice, corrective efforts, such as: controlling the behavior of students, checking the condition of students, communication with parents, and doing individual approaches (4) The obstacle experienced by teachers in dealing with student misbehavior is the lack of support and attention of parents towards student behavior.